2018
DOI: 10.1530/ec-18-0014
|View full text |Cite
|
Sign up to set email alerts
|

Fetal over- and undernutrition differentially program thyroid axis adaptability in adult sheep

Abstract: ObjectiveWe aimed to test, whether fetal under- or overnutrition differentially program the thyroid axis with lasting effects on energy metabolism, and if early-life postnatal overnutrition modulates implications of prenatal programming.DesignTwin-pregnant sheep (n = 36) were either adequately (NORM), under- (LOW; 50% of NORM) or overnourished (HIGH; 150% of energy and 110% of protein requirements) in the last-trimester of gestation. From 3 days-of-age to 6 months-of-age, twin lambs received a conventional (CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Given that the fetus relies heavily on maternal thyroid hormone, it is possible that maternal thyroid hormone dynamics may influence the offspring's phenotype through developmental programming. 120 Rae et al found that when pregnant sheep were fed a low-calorie diet, tT3 concentrations were significantly lower in both maternal and fetal plasma. 121 The authors raise the possibility that thyroid hormones may play a role in mediating the effects of maternal undernutrition on fetal development.…”
Section: Hypothesesmentioning
confidence: 99%
“…Given that the fetus relies heavily on maternal thyroid hormone, it is possible that maternal thyroid hormone dynamics may influence the offspring's phenotype through developmental programming. 120 Rae et al found that when pregnant sheep were fed a low-calorie diet, tT3 concentrations were significantly lower in both maternal and fetal plasma. 121 The authors raise the possibility that thyroid hormones may play a role in mediating the effects of maternal undernutrition on fetal development.…”
Section: Hypothesesmentioning
confidence: 99%
“…h) 'Programming' future reproductive performance -from gamete to embryo to fetus The concept of 'Developmental Origins of Health and Disease' (DoHaD) began with the epidemiology of maternal undernutrition in humans and was then extended to farm animals (review: Sinclair et al, 2016). There is now strong evidence for 'programming' of diverse aspects of future health and productivity in sheep (Figure 2) -eg, the quantity and quality of wool, milk and meat produced (eg, Kelly et al, 2006;van der Linden et al, 2009;Sen et al, 2015); cardiovascular health, salt tolerance, thyroid function, and glucose homeostasis (Gopalakrishnan et al, 2004;Chadwick et al, 2009;Jaquiery et al, 2016;Johnsen et al, 2018). Interestingly, the DoHaD hypothesis began with a focus on the fetus but has now been extended back to before fertilization because there is evidence that undernutrition also causes effects in the oocyte and embryo that have consequences for postnatal life (Ashworth et al, 2009;Jaquiery et al, 2012).…”
Section: G) Embryo Mortalitymentioning
confidence: 99%
“…As fetal thyroid gland differentiates between 75 and 90 dpc, maternal dietary restriction during early-gestation may reset the physiology of the HPT axis by altering ontogeny of the thyroid 71 . This is reflected in increased free T3 (FT3) levels in the neonatal calf 10 and lamb 72 .…”
Section: Neonatal Adaptationmentioning
confidence: 99%